(untitled) - Nimmo, William F. (New York, 1988)
Most Americans are unaware that Soviet forces detained and imprisoned Japanese soldiers and civilians on a massive scale following World War II. In addition to interning large numbers of Japanese nationals in Soviet-occupied territories, the Red Army deported more than half a million Japanese to labor camps in Siberia and other parts of the USSR. Despite efforts to gain their release, repatriation was not complete until 1956. Nimmo's book is the first work in English to provide a detailed account of this little-known aspect of the war's aftermath.
Keywords: World war, 1939-1945,Prisoners of war,Prisoners of war,Forced labor; Prisoners and prisons, soviet.,History; 20th century; Soviet union,Japan,Soviet union